The process of successful ageing. - Baltes, Margret M.; Carstensen, Laura L. (Ageing & Society, 1996)
The writers advocate a process-oriented approach to successful aging. They argue that understanding the processes used by people to reach their goals under increasing limitations in social, psychological, or biological resources will result in additional insights and progress in the field. They contend that the metamodel of selective optimization with compensation proposed by Baltes and Baltes (1990) offers a suitable framework within which to pose questions such as what successful ageing is, how people age successfully, and what the processes are that allow for mastery of goals in old age. The model presented takes gains and losses jointly into account, pays attention to the great heterogeneity in aging and successful aging, and regards successful mastery of goals in the face of losses endemic to advanced age as the result of the interplay of the processes of selection, compensation, and optimization.